Change of Ownership and Time of Recording in National Accounts. (IMF Working Papers; Working Paper ;, 1988)
This paper establishes 'economic ownership' as a crucial concept in analyses of the flows of goods and services in the production and consumption processes, and of income to the factors of production. The paper argues that an approximation to economic ownership or control is legal ownership, which will serve in most cases but requires modification when legal title is established for taxation or regulatory purposes unrelated to economic risks of ownership. It is recommended that national accounting standards recognize the economic ownership concept and be consistent and flexible in its implementation to avoid asymmetry yet accommodate evolving commercial accounting practices.